1993
DOI: 10.1161/01.str.24.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow alterations in a rat model of cerebral sinus thrombosis.

Abstract: Outcome from sinus vein thrombosis is very variable, with symptoms from headache to coma. Experimental findings suggest that an involvement of cortical veins is necessary to affect the cerebral microcirculation. Laser Doppler flowmetry was used to investigate the regional and temporal changes in local cortical blood flow after experimental occlusion and thrombosis of the superior sagittal sinus and tributary cortical veins in rats. Thrombosis was induced by slow injection of kaolin-cephalin suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 28 publications
1
48
0
2
Order By: Relevance
“…10 Alternatively, previous experimental studies showed that retrograde venous pressure might counteract capillary perfusion pressure to decrease cerebral blood flow, and thus cause arterial ischemia resulting in cellular or cytotoxic edema. 12,21 Previous experimental and clinical diffusion-weight imaging studies of cerebral venous thrombosis have shown that ADC value was decreased, 12,22,23 normal, 23 increased, 24 or heterogeneous. 25,26 The ADC values decreased by 56% at 30 minutes after experimental cerebral venous thrombosis, and secondary increases in ADC subsequently developed in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…10 Alternatively, previous experimental studies showed that retrograde venous pressure might counteract capillary perfusion pressure to decrease cerebral blood flow, and thus cause arterial ischemia resulting in cellular or cytotoxic edema. 12,21 Previous experimental and clinical diffusion-weight imaging studies of cerebral venous thrombosis have shown that ADC value was decreased, 12,22,23 normal, 23 increased, 24 or heterogeneous. 25,26 The ADC values decreased by 56% at 30 minutes after experimental cerebral venous thrombosis, and secondary increases in ADC subsequently developed in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, venous ischemia also has specific characteristics, such as an early bloodbrain barrier disruption and an increase of the net capillary filtration, that may result in early vasogenic edema. 19,24 In our patient, the contrast between slight DWI abnormalities and marked FLAIR abnormalities may reflect prominent and early vasogenic edema associated with mild cytotoxic edema.…”
Section: Discussionmentioning
confidence: 99%
“…13,22,23 The analysis of flow observation frequency histograms allows discrimination of the different effects of acetazolamide on microcirculation and on larger cortical vessels. A detailed correlation of anatomic structures and lCBF findings (S. Kroppenstedt, MD, unpublished data, 1997) shows that the most pronounced flow increase occurs in regions with a flow Ͻ60 LDU (microcirculation), while the flow in the vicinity of larger vessels remains largely unaffected.…”
Section: Discussionmentioning
confidence: 99%